Testing of full scale composite journal bearings for offshore underwater applications: - Dragt, R.C.; Van Den Heuvel, W.; Gelinck, E.R.M.; Slot, H.M. (American Society of Mechanical Engineers (ASME), 2015)
In the offshore industry, fibre reinforced sliding journal bearings are increasingly used due to their low-maintenance and self-lubricating characteristics. To be able to use the bearings in the rough offshore environment, under heavy loading, full scale tests are essential to assess the friction and wear rate development during use. For this purpose, two full scale wear tests were performed on composite sliding journal bearings of 300 mm in diameter. These tests were performed at the laboratory of TNO Structural Dynamics in Delft, The Netherlands, over a period of eight months. For this purpose, a test rig was designed in which a shaft runs through the journal bearing. The latter is loaded in the range 50 to 700 kN and the shaft is given triangle-like cyclic displacements. To be able to test under realistic conditions, the bearing is constantly submerged in flowing seawater. Forces, displacements and temperatures were constantly monitored to manage the system and determine the parameters. Besides a description of the test rig, a rationale of choices made, observations during testing and detailed cycle-by-cycle friction characteristics are presented, next to generalized trends for the wear and Coefficients of Friction (CoFs) under the various loading conditions. © 2015 by ASME.